True Giant Posterior Tibial Artery Aneurysm - Alessandro Robaldo; Giacomo Di Iasio; Gabriele Testi; Patrizio Colotto (Case Reports in Surgery)
We report an unusual case of true atherosclerotic posterior tibial artery (PTA) aneurysm without any apparent causative history. To our knowledge, in the English Literature only seven previously cases of true PTA aneurysms are reported. Due to its location, this lesion may require surgical intervention and removal. The presentation, the diagnostic evaluation, and the surgical management of the aneurysm are discussed.